Firm and labour adjustments to FDI liberalisation - Ming-Jen Lin; Yi-Ting Wang; Sung-Ju Wu (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2025)
This paper studies how liberalising outward foreign direct investments (FDI) affects manufacturers' engagement in global production and their domestic workers' labor market outcomes. Focusing on a liberalisation policy in 2001 by the government of Taiwan that allowed 122 electronic products to be produced in China, we estimate its effect on Taiwanese electronic manufacturers and their domestic workers. Employing a matched difference-in-differences strategy, we find that the manufacturers targeted by the policy were on average 14% more likely to invest in China relative to the non-targeted ones. Correspondingly, the domestic incumbent workers of the targeted manufacturers were on average more likely to change their jobs, stay employed for fewer years, and have lower wages in subsequent years relative to those employed by the non-targeted ones. The worker-level effects of the policy exhibited substantial heterogeneity across the initial wage distribution, with the top-decile workers benefiting and the other workers losing on average.
Keywords: 330